2013
DOI: 10.1186/1751-0147-55-4
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the ability of Dichelobacter nodosus to survive in soil

Abstract: BackgroundDichelobacter nodosus is the causative agent of footrot in sheep. The survival of the bacterium in soil is of importance for the epidemiology of the disease. The investigation evaluates the survival of D. nodosus in soil with and without added hoof powder stored under different temperatures.ResultsAn experimental setup was used with bacteriological culture and real-time polymerase chain reaction (PCR), and the results indicate that the bacteria can survive in soil for longer time than previously expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…3 ). It is not clear why these two results appear contradictory, but a laboratory study of survival of D. nodosus in small soil microcosms indicated that survival is longer at 5 °C than 15 °C ( Cederlof et al., 2013 ). Other key factors for survival and transmission include moisture level (the farm studied here had high rainfall), soil type and possibly localised evolution of D. nodosus strains ( Russell et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 ). It is not clear why these two results appear contradictory, but a laboratory study of survival of D. nodosus in small soil microcosms indicated that survival is longer at 5 °C than 15 °C ( Cederlof et al., 2013 ). Other key factors for survival and transmission include moisture level (the farm studied here had high rainfall), soil type and possibly localised evolution of D. nodosus strains ( Russell et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Housing ewes in the barn at higher stocking density for the 3-month period around lambing (up to week 30) likely contributed to increased FR prevalence and severity. It is known that environmental factors play an important role in determining infection rate and progression of FR severity, with heavier infection rates occurring under warm moist conditions [50] - [52] . Dichelobacter nodosus , one of the main organisms associated with FR is an anaerobic and fastidious bacterium that colonizes the interdigital epithelial tissue more readily during the wet seasons of spring, fall, and winter.…”
Section: Discussionmentioning
confidence: 99%
“…In summer the temperature rises as high as 37 o C. During winter the temperature stays below 12.6 o C. The humidity varies between 71% and 90% (http://www.mymensingh.gov.bd). This environmental condition is favourable for the survival of both Dichelobacter nodosus and Fusobacterium necrophorum (Cederlof et al, 2013). This may contribute to the higher prevalence (4.2%) of ovine footrot in this region (Table 1).…”
Section: Resultsmentioning
confidence: 99%